Analysis Of Land Use Change And The Suitability For Regional Spatial Planning (RTRW) In Kolaka District - Sanjaya, Rifky; Sudia, La Baco; Gandri, La; Indriyani, Lies; Ahmaliun, La De (Journal of Soilscape and Agriculture, 2024)
Land use changes that occur due to population pressure and land conversion that are not in accordance with the RTRW will affect the sustainability of the development of an area. In the period 2003 to 2013, it is known that land changes occurred in Kolaka sub-district, namely that the production forest experienced a reduction in area of ​​266.26 Ha of the total land area, which was converted into dry land. Some possibilities include land conversion from forest area to plantation land by residents. Meanwhile, in the period 2013 to 2023, Production Forests became land with a very large degraded area, where an area of ​​1884.48 ha was converted into wetlands, dry lands, and as limited production forests. The condition of this land use change was then analyzed for its suitability to the 2012 - 2023 RTRW of Kolaka Regency. It was found that 75.53% or an area of ​​10,579.55 ha of the existing area was still suitable, while the unsuitable area was 24.47% or an area of ​​3426.91 ha.